Anxiety among fathers during the prenatal and postpartum period: a meta-analysis. (3rd April 2021) - Leiferman, Jenn A.; Farewell, Charlotte V.; Jewell, Jennifer; , Rachael Lacy; Walls, Jessica; Harnke, Benjamin; Paulson, James F.
Abstract: Introduction: The purpose of this review was to determine the prevalence of anxiety among fathers during the perinatal (pre- and post-natal) period. Methods: A systematic search was conducted to identify studies published between 1995–2020. One hundred and seventy-two of the records met inclusion criteria and full texts were screened for eligibility. The authors followed PRISMA guidelines to extract the data. Results: A total of 23 studies, representing 40, 124 participants, are included in this meta-analysis. The overall random effects estimate of paternal perinatal anxiety was 10.69% (95% confidence interval (CI): 8.14 − 13.91%). Rates of paternal perinatal anxiety demonstrated significant heterogeneity that was large in magnitude ( Q  = 304, 494, p < .001, I 2  = 99.93 and τ 2 = .5381). Study quality rating did not appear to moderate rates of paternal perinatal anxiety (low: 10.74%; 95% CI: 6.56–17.11%; high: 10.65%; 95% CI: 6.02– 18.15%). Discussion: Paternal perinatal anxiety rates in this meta-analysis are considerably higher than the global WHO regional prevalence rates for anxiety among men suggesting the transition into parenthood may place men at greater risk for anxiety.